Analysis of cracking behavior of 440C stainless steel during rotary tube piercing process - Yu Zhang; Jianguo Wang; Dong Liu; Jungang Nan; Haodong Rao; Yaqi Lai; Yonghao Zhang (Results in Engineering)
The preparation of 440C stainless steel tubes by rotary tube piercing (RTP) process is still difficult due to the cracking sensitivity of 440C stainless steel in the process of hot deformation. The seamless tube piercing process of 440C stainless steel is addressed in this paper by comparing rolling experiments, hot tensile tests, and finite element method (FEM). Based on the high-temperature tensile test, the mechanical properties of 440C stainless steel under different deformation conditions was evaluated. The results from the rolling experiments indicated that the cracking behavior at the head position of the tube was predominantly a plastic damage process dominated by tensile stress. It was found that in regions enriched with carbides, substantial nucleation of voids occurs, which subsequently aggregate directly, facilitated crack propagation. The distribution of strain, strain rate, temperature, and stress triaxiality during the forming process of 440C stainless steel seamless tubes was discussed through FEM. A comprehensive analysis of these results reveals that during the RTP process, the Mannesmann effect, combined with the strain rate gradient at the tube ’s inner surface, induces the initiation and propagation of cracks. In addition, 440C stainless steel demonstrates distinct microvoid evolution behaviors under varying deformation conditions, which contributes to a deeper understanding of the hot deformation failure mechanisms.